A novel dual-cytokine–antibody fusion protein for the treatment of CD38-positive malignancies. Issue 5 (5th July 2018) - De Luca, Roberto; Kachel, Paul; Kropivsek, Klara; Snijder, Berend; Manz, Markus G; Neri, Dario
Abstract: A novel dual-cytokine–antibody fusion protein, consisting of an antibody directed against CD38 [a tumor-associated antigen mainly expressed on the surface of multiple myeloma (MM) cells], simultaneously fused to both tumor necrosis factor ligand superfamily member 10 (TRAIL) and interleukin-2 (IL2), was designed, expressed and purified to homogeneity. The novel fusion protein, termed IL2-αCD38-αCD38-scTRAIL, was able to selectively recognize its cognate antigen expressed on the surface of MM and lymphoma cell lines, as evidenced by flow cytometry analysis. Moreover, the targeted version of TRAIL was able to induce cancer cell death in vitro, both with MM cell lines and with fresh isolates from the bone marrow of MM patients. The experiments provide a rationale for possible future applications of IL2-αCD38-αCD38-scTRAIL for the treatment of patients with MM or other CD38-positive malignancies.